A Global History of Pre-Modern Warfare : Before the Rise of the West, 10,000 BCE-1500 CE - Roy, Kaushik (Cass Military Studies, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Preface and acknowledgements -- List of maps -- Glossary -- Introduction: evolution of warfare before the rise of the West -- 1 The origins of warfare -- 2 Military convergence and the Bronze Age civilisations of Eurasia -- 3 Military divergence in Eurasia: Classical Greece against Persia -- 4 The era of hybrid military machines: Macedonia, the Hellenistic monarchies, India and China -- 5 Military divergence again: Rome, Carthage, Parthia, India and the Far East -- 6 Military convergence in medieval Eurasia -- 7 Convergence or divergence? Naval warfare in medieval Eurasia -- 8 Evolution of warfare beyond Eurasia -- Conclusion -- Index.